2002
DOI: 10.1182/blood.v99.7.2337
|View full text |Cite
|
Sign up to set email alerts
|

The effects of postponing prophylactic treatment on long-term outcome in patients with severe hemophilia

Abstract: To prevent hemophilic arthropathy, prophylactic treatment of children with severe hemophilia should be started before joint damage has occurred. However, treatment is expensive, and the burden of regular venipunctures in young children is high. With the aim of providing information on starting prophylaxis on the basis of individual patient characteristics, the effect of postponing prophylaxis on longterm arthropathy was studied in a cohort of 76 patients with severe hemophilia born between 1965 and 1985. The m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
237
0
3

Year Published

2003
2003
2017
2017

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 239 publications
(249 citation statements)
references
References 23 publications
9
237
0
3
Order By: Relevance
“…In addition, long-term studies in which animals were injected with blood have shown that cartilage matrix is adversely affected (18,19). Moreover, these data corroborate clinical findings that a limited number of joint hemorrhages in childhood, before the initiation of prophylactic treatment, may result in joint damage more than a decade later (10). Whether the changes observed in the present study will indeed lead over a period of years to fullblown joint damage remains to be investigated.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…In addition, long-term studies in which animals were injected with blood have shown that cartilage matrix is adversely affected (18,19). Moreover, these data corroborate clinical findings that a limited number of joint hemorrhages in childhood, before the initiation of prophylactic treatment, may result in joint damage more than a decade later (10). Whether the changes observed in the present study will indeed lead over a period of years to fullblown joint damage remains to be investigated.…”
Section: Discussionsupporting
confidence: 87%
“…In the clinical setting it has been shown that early treatment of joint bleedings in patients with hemophilia may protect against arthropathy in later years; starting treatment with clotting factors after the third joint hemorrhage during early childhood results in better clinical outcome after 22 years of followup (10). However, this early prophylaxis cannot completely prevent arthropathy.…”
mentioning
confidence: 99%
“…These data in a large prospective cohort confirm earlier results of smaller retrospective analyses. [13][14][15] Therefore, primary prophylaxis, or the prevention of joint damage by prevention of any joint hemorrhage is the only therapy effective to preserve joint structure and function. In addition, in over 12 years of observation, there was no observed benefit of prophylaxis to regain previously lost joint motion.…”
Section: Discussionmentioning
confidence: 99%
“…3,4 These strategies are reflected in the two most frequently used definitions of primary prophylaxis. The European Pediatric Network for Hemophilia Management (PedNet) first specified primary prophylaxis as starting before two years of age OR before the second joint bleed, 5 and The World Federation of Hemophilia (WFH) as starting before the age of three years AND before the second joint bleed, in the documented absence of osteochondral joint disease.…”
mentioning
confidence: 99%